Gambaran Kesiapan Mengajar Guru Kelas di Sekolah Inklusif - Farida Kurniawati; Ambar M.R.S (Fakultas Psikologi Universitas Pancasila, 2011)
In inclusive education practices, several aspects determine the quality of teaching process. One of them is teaching resources. This study aims to assess teacher's readiness in inclusive schools, based on how they employ their tasks in the inclusive setting. According to PLB Directorate Guide Book (2004d). and Hallahan and Kauffman (1994), those tasks are (1) to create a conducive learning environment; (2) to construct and implement assessment to all children in order to identify every child's needs, strengths, and weaknesses; (3) to design an Individualized Education Program (IEP) and accommodate every child's needs; (4) to collaborate with all related parties; (5) to teach and evaluate; and (6) to manage classroom administration. The study shows that all respondents can employ those tasks. However, there are some flaws in the implementation, particularly on tasks involving direct relations with special-need children, such as (1) IEP and (2) teaching strategies and tools. These flaws are usually due to the classroom teachers' limited knowledge, and school's failure to provide adequate facilities for all children's needs, especially children with special needs. Thus, to be able to do their tasks optimally, teachers need positive attitude; a sufficient knowledge about special-need children and inclusive school; skills and socialization; and adequate facilities. It is necessary for the next study to employ observational methods as the main tool, and utilize a quantitative approach to complement this study.